Antibiotics usage, how well we know it? KAP survey among the dentist population in Mumbai - Parekh, Amisha N.; Balasubramanian, Karthik; Bhate, Purvi; Kalra, Dheeraj D. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: There is a rising concern for antibiotic resistance worldwide, the primary cause of which is overuse and misuse. This study primarily aimed at assessing the knowledge of dental practitioners regarding the current guidelines on use of antibiotics and to identify the shortcomings if any. Methods: Present study was a cross-sectional questionnaire-based study conducted amongst 450 dental practitioners across Mumbai with the help of a self-designed questionnaire. The data was entered into excel sheets and appropriate statistical analysis was done with chi-square test using SPSS version 20. Results: The present study had a response rate of 95%. For the total percentage of patients examined each day that required systemic antibiotics, 36.9% (153) dentists answered 0-5%, followed by 25.3% (105) answered 10-15%. 76.1% (316) dentists came across patients who had self-prescribed antibiotics. 66% (274) dentists had never advised an antibiotic sensitivity/ culture test for their patients. 51.3% (213) dentists came across patients who did not respond to antibiotics. 87.2% (363) dentists were not aware about the ‘AWaRe’ classification of antibiotics given by WHO. 93.3% (383) dentists did not know about antimicrobial stewardship concept. Conclusions: The present study reflected antibiotic overuse and misuse to a certain extent by dental practitioners across Mumbai. Most dentists were unaware about ‘AWaRe’ classification and antimicrobial stewardship. Patient education on ill effects of self-prescription of antibiotics, identification of traits of antibiotic resistance and antibiotic culture tests needs to be prioritized by dentists.